Human(itarian) Capital? Lessons on Better Connecting Humanitarian Assistance and Social Protection - Gentilini, Ugo (World Bank E-Library Archive, 2018)
Governments in low and middle-income countries are increasingly investing in social protection, and also address many of their own people's 'humanitarian' needs themselves. For their international partners, who may have an important role in filling gaps when household needs exceed national capacity to meet them, support for the strengthening of national systems, combined with a shift from short-run to more durable approaches, is becoming a unifying framework for assistance. Some aspects of social protection and humanitarian assistance therefore seem to be on a converging trajectory. 'Human(itarian) Capital?' discusses findings from twelve country case studies exploring the linkages between humanitarian assistance, in its various interpretations, and national social protection systems. Specifically, the paper distills lessons on how humanitarian assistance and social protection systems might better coexist, the possible challenges and trade-offs emerging from practical experiences, and how to facilitate, inform, and accelerate future concerted action